PDCT-09. PHASE 1/2 STUDY OF DSP-7888 IN PEDIATRIC PATIENTS WITH MALIGNANT GLIOMA. (5th November 2018) - Fujisaki, Hiroyuki; Hashii, Yoshiko; Terashima, Keita; Goto, Hiroaki; Horibe, Keizo; Sugiyama, Kazuhiko; Watanabe, Akinobu; Sugimoto, Saori; Yanagisawa, Takaaki; Kikuta, Atsushi; Kawamoto, Hiroshi; Hashimoto, Naoya; et al.
Abstract: BACKGROUND: DSP-7888 is an experimental cancer vaccine containing peptides that induce WT1-specific CTLs and helper T cells. A phase 1/2 study in pediatric patients (pts) with malignant glioma was conducted to evaluate the efficacy and safety. METHODS: Diffuse intrinsic pontine glioma (DIPG), glioblastoma (GBM) and other high grade glioma (HGG) pts for whom standard therapy failed or who have no available standard therapies were eligible. Pts received five-times DSP-7888 3.5 mg/body via intradermal injection weekly followed by biweekly administration. Response was assessed with MRIs via modified RANO criteria. Recommended dose was determined based on the traditional 3 + 3 design. RESULTS: Four pts were enrolled in phase 1 dose finding part (3.5 mg/body). One patient was replaced due to primary disease progression and the three pts completed DLT evaluation and no DLTs were observed. Therefore, recommended dose was determined as 3.5 mg/body. In a whole study, 18 pts (11 DIPG, 5 GBM and 2 HGG) were enrolled. There was no dose-limiting or unexpected toxicity. Most common treatment related adverse events was controllable injection site reaction only. Disease control (CR+PR+SD) was observed in 7 of 18 pts, with 1 PR and 6 SD. Median OS from initial dose in DIPG exceeded 5 months. Three out of 5 GBM pts are on survival more than 11 months. WT1 specific CTLs induction were observed in several pts. CONCLUSIONS: DSP-7888 is well tolerated at 3.5 mg/body for pts with pediatric malignant glioma. Survival results in DIPG pts exceeded in comparison with historical controls. Moreover, some GBM pts shows encouraging sign of long survival.